The modification and testing of an anatomically shaped radius and ulna interlocking intramedullary nail using statistical shape modelling derived from computed tomography scans. - Pretorius, Henry Sean (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.